Corn Response as Affected by Planting Distance from the Center of Strip-Till Fertilized Rows - Adee, Eric; Hansel, Fernando D.; Ruiz Diaz, Dorivar A.; Janssen, Keith (Frontiers in Plant Science, 2016)
Strip-till has been used at a large scale in east central Kansas as an alternative to earlier planting dates under a no-till system. To determine the effects of planting corn (Zea mays) under previously established strip-tilled fertilized rows, experiments were conducted on an Osage silty clay loam soil in 2006 and 2008 and on a Woodson silt loam soil in 2009, 2010, and 2011 using three different planting distances from the strip-tilled fertilized rows (0, 10, 20, and 38 cm) with a strip-till operation performed between 1 and 73 days before planting. The depth of the strip-till fertilizer application was 13–15 cm below the soil surface. Corn that was planted 10 cm from the fertilized row showed greater early season growth, higher plant population, and grain yield. Planting 20 and 38 cm from the center of the fertilized rows showed none of the benefits that are typically associated with strip-tillage system. Enough time should be allowed between the strip-till operation and planting to reach satisfactory soil conditions (e.g., moist and firm seedbed). Our results suggest that the best location for planting strip-tilled fertilized corn vary depending on soil and climatic conditions as well as the time between fertilizer application with the strip-till operation and planting. With fewer number of days, planting directly on the center of fertilized strip-till resulted in decreased plant population and lower grain yield. However, the greatest yield benefit across different planting conditions was attained when planting within 10 cm of the strip.